Phenotypic and metabolic aspects of prostatic epithelial cells in aged gerbils after antisteroidal therapy: Turnover in the state of chromatin condensation and androgen-independent cell replacement - Campos, Silvana G.P.; Gonçalves, Bianca F.; Scarano, Wellerson R.; Góes, Rejane M.; Taboga, Sebastião R. (Elsevier, 2013)
The gerbil is a rodent considered a good model for studies of prostatic morphophysiology under different experimental conditions. Studies involving castration and steroidal blockers of aged gerbils showed that the glandular epithelium persists after long-term therapy, preventing the organ atrophy. Thus, the objective of this study was to evaluate the phenotypic characteristics and behavior of prostatic epithelial cells that remained after different periods of hormone ablation in aged gerbils. The identification of elements that influenced the survival of this cell type was performed by morphometric, nuclear phenotypes, ultrastructural and immune histochemical analysis. The most significant responses to treatment, by analyzing morphometric features, were observed during the first three time points (day 1, day 3, and day 7), after which there appeared to be an adjustment of the gland to the hormone ablation. All treatments led to changes in the state of chromatin condensation, DNA methylation pattern and phenotypic changes indicated cell senescence. Additionally, an increase in the basal cells seemed to guarantee self-renewal properties to the epithelium. These data indicate that changes occur at many levels, including gene expression and nuclear architecture in the epithelial cells, when aging and steroidal blockade are associated. These aspects are important when considering castration-resistant prostate cancer, a malignant tumor posing difficult therapeutic intervention. © 2013 Elsevier GmbH. All rights reserved.
Keywords: 5-Methylcytidine; Aged gerbil; Antisteroidal therapy; Karyometry; p63; Prostate; Transmission electron microscopy